Analisis Kesulitan Membaca Permulaan Siswa Kelas 1 Sekolah Dasar - Mitra Rahma; Febrina Dafit (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to explain the difficulty of reading at the beginning of grade 1 at SDN 022 Pulau Baru Kopah. This type of research is descriptive qualitative research. The subjects of this study were class 1A teachers and class 1A students. Data collection techniques used are interviews, observation and documentation. The data analysis technique uses the Milles and Huberman model with stages, data reduction, data presentation, and drawing conclusions. The results showed that 47.6% of students who had difficulty reading the beginning were, (1) students did not recognize letters, (2) could not read syllables, (3) could not read word for word, (4) could not read diphthongs, clusters and diagraphs, (5) cannot read consonants, (6) cannot read vowels, (7) series, (8) wrong prephasers, (9) do not know the meaning of words. The solution given by the teacher to overcome the difficulty of early reading is to provide additional hours, pay more attention to students who have difficulty reading the beginning and teach students to recognize letters with creative techniques such as singing, students are asked to write sentences and aloud and so on.